Utilization of sun-dried on-farm generated poultry litter as a feed resource for growing-finishing pigs - A. O. K. Adesehinwa; O. O. Obi, B. A. Makanjuola; A. O. Adebayo; E. S. Durotoye (African Journal of Pig Farming, 2017)
Forty eight (48) growing-finishing pigs (36.11 ± 1.26 kg) were allotted to three dietary treatment groups of 0, 33.33 and 66.67% sun-dried on-farm generated poultry litter (SOPL) as a replacement for 30% maize in diets of growing-finishing pigs on weight basis to assess its implication on the chemical composition of the feed, growth performance and blood chemistry of the pigs. Each treatment was replicated four times with 4 pigs/replicate in a completely randomized design. The diets were formulated to contain 16 - 19% crude protein and the pigs housed in concrete floored pens containing feeding and watering troughs for the duration of the study. The results obtained in this study revealed some numerical differences in the crude protein and fibre contents of the SOPL diets over the control diet. Increases were also recorded in the acid detergent fibre (ADF), neutral detergent fibre (NDF) and acid detergent lignin (ADL) fractions of the diets as a result of the replacement levels of SOPL. Daily weight gains and the efficiency of feed utilization of the growing pigs were not significantly (P > 0.05) influenced by the graded levels of SOPL. Replacement of maize with 33 and 66% SOPL resulted in 10.4 - 20.9% reduction in the cost of feed/kg. This in turn resulted in 15 - 25% reduction in the cost of feed required for an additional kg gain/pig when the graded levels of SOPL was fed to the pigs. An increased level of up to 66% SOPL resulted in a depression (P < 0.05) in the values of packed cell volume (PCV) and white blood cells (WBC) while the hemoglobin, serum glucose, urea, creatinine and glutamate pyruvate transaninase values of the pigs across the groups were unaffected (P > 0.05). However, variations recorded in the values of the red blood cells (RBC) and alkaline phosphatase did not follow any particular trend. The values of the serum total protein, albumin and cholesterol values increased significantly (P < 0.05).